Passion's way (Freyda Rosthstein Production, 1999)
In life you have one true, pure love. One person who captures your heart, and gently touches your soul. For Charles Darrow, this person is Anna Leath and for Anna, this person is Charles. Years ago, their lives strayed apart. Now they are about to reunite.